Implementasi Supervisi Klinis dalam Peningkatan Kompetensi Pedagogik Guru Mata Pelajaran Pendidikan Agama Islam - Amir, Asmah; Hajar, Andi (CV. Creative Tugu Pena, 2022)
This research is a study on the implementation of clinical supervision in increasing the pedagogic competence of teachers of Islamic Religious Education subjects at Madrasah Aliyah Negeri (MAN) 2 Bone. The article was to find out how the urgency of the implementation of clinical supervision, its implementation strategy and the implications of clinical supervision on increasing the pedagogic competence of teachers of Islamic Religious Education subjects at Madrasah Aliyah Negeri (MAN) 2. The researchers used qualitative research.The research instrument is the researcher as the main instrument. The collecting data used observation, interviews, and documentation. The processing technique uses qualitative data analysis which is carried out interactively and continuously through the process of data collection, data reduction, data presentation, and data verification or drawing conclusions. The results showed that the urgency of clinical supervision helps teachers in analyzing various problems and finding solutions in relation to various learning process activities. Meanwhile, the strategy for implementing clinical supervision of teachers is very important to be used to solve every problem, both in making the stages of Kegiatab Belajar Mengajar (KBM) planning, implementation and monitoring and evaluation. The implications of clinical supervision on increasing the pedagogic competence of teachers of Islamic Religious Education subjects at MAN 2 Bone have an impact on the understanding and skills of teachers in using and creating learning media. However, in the administration of learning and learning activities, there are still manye teachers who copy and paste the lesson plans (friends or from the previous year). In addition, only a small number of teachers use assessment instruments, and are not even able to compile and analyze assessments. This also has an impact on student achievement because learning activities are not carried out effectively and efficiently. Keywords: Clinical Supervision, Pedagogic Competence, Increasing Pedagogic Competence